Characterization of Arrowhead-Derived Type 3 Resistant Starch Prepared by Ultrasound-Assisted α-Amylase Degradation. (3rd January 2023) - Sun, Jian; Sun, Liangge; Chen, Xinxiang; Raza, Husnain; Wu, Gangshan; Liang, Qiufang; Ren, Xiaofeng
Abstract : The effect of ultrasonic-assisted α -amylase hydrolysis on the structure and physicochemical properties of arrowhead-derived type 3 resistant starch (RS3) was studied. After ultrasound treatment, the yield of resistant starch reached 17.21%, significantly (p < 0.05 ) increased by 65.64%. Compared with RS3 prepared by traditional enzymolysis (RS3-E), the crystal form and chemical bond of RS3 prepared by ultrasonic-assisted enzymolysis (RS3-UAE) did not change, but its gelatinization temperature, relative crystallinity, enthalpy, and 1047/1022 values were improved to varying degrees. RS3-UAE exhibited a higher solubility, transparency, water absorption capacity, and higher swelling power at 70°C. The analysis results of iodine absorption, differential scanning calorimetry, X-ray diffraction, Fourier transform-infrared spectroscopy, and scanning electron microscopy demonstrated that RS3-UAE exhibited a more regular shape, smoother surface, higher crystallinity, stable double helix structure, and more ordered and denser structure. Therefore, ultrasound-assisted enzymatic technology is an effective way to prepare RS3, and it can improve the functional and structural properties of the prepared RS3 to a certain extent.